The Diversity of Russia's Arctic Cities - Badina, Svetlana (DEU, 2024)
This article describes the diversity of Russia's Arctic cities. As a group, Russia's northern urban agglomerations are larger than those found in the West. But there is enormous diversity among them that makes the region one of the most dynamic in the Russian Federation.